Effectiveness of postnatal practice of breast care and breast Feeding technique among hospitalized antenatal mothers - C. MUTHU LAKSHMI (International Journal of Pharma and Bio Sciences, 2016)
Breast milk is nature’s way of providing all nutritious those new born needs in the right amounts and proportions till the infant reaches 4-6 months of age. No other types of animal milk or milk formula can substitute for this breast milk. To assess the effectiveness of prenatal teaching programme on postnatal practice of breast care and breastfeeding on the first postnatal day and third postnatal day in experimental and control group. To find the association between postnatal practice and selected demographic variables of mothers in experimental group. An evaluative research was found to be appropriate for the study. An arbitrary decision was taken to keep the sample size as 60. 30 antenatal mothers were recruited in experimental group and 30 in control group Overall postnatal practice mean score among primi, LSCS, multi on 1st postnatal day regarding breast care were 22.6, with ‘t’ value 14.92 (p<0.01) were highly significant in the experimental group than control group Overall postnatal mean score among primi, LSCS, multi on 3rd postnatal day regarding breast care were 23.6 with ‘t’ value = 39.5 (p<0.01), for breast feeding the overall mean score among primi, multi, LSCS on 3rd postnatal day were 23.7 with ‘t’ value = 15.83 (p<0.01) were highly significant in the experimental group than control group.